Operating Room Management after 2008 Economic Crisis in Italy: A Literary Review - Rochira, Andrea; Ubiali, Andrea; Buccioli, Matteo; Perger, Peter (KnE Social Sciences, 2020)
The 2008 financial crisis has changed administration methods of various activities and productive services, including health services. In fact in Italy it was necessary a deep reorganization of the healthcare system due to a strong reduction in the funds allocated to the health sector. Consequently the management of the hospital operative theaters like operating rooms (OR) has become a priority aspect in the health administration. In this context we performed a literary review about experiences or projects of operating room management (ORM) carried out in Italy between 2007 and nowadays. We searched Medline database and we found 12 articles meeting the inclusion criteria. Only one paper was submitted in 2007, the remain were drafted in the following years. The italian regions represented are mostly of the north center area. The topics discussed are heterogeneous: ORM reorganizations in clinical hospitals, simulations of models aimed to resolve OR slots assignment, surgical waiting lists management, OR process analysis and ORM literary review. Overall the results show that interest and competence for the ORM are quickly increasing in Italy. In fact, because OR are the most expansive and the most productive areas of every hospitals, it’s of paramount relief to implement strategies in order to optimize OR quality and minimize the non-productive and unnecessary costs, especially in the current period of austerity measures and continuous cuts to public funds. Keywords: hospitals, management, crisis, resources, surgery, healthcare, ORM